From an Fe2P3 complex to FeP nanoparticles as efficient electrocatalysts for water-splitting. Issue 45 (24th September 2018) - Yao, Shenglai; Forstner, Viktoria; Menezes, Prashanth W.; Panda, Chakadola; Mebs, Stefan; Zolnhofer, Eva M.; Miehlich, Matthias E.; Szilvási, Tibor; Ashok Kumar, Nanjundan; Haumann, Michael; Meyer, Karsten; Grützmacher, Hansjörg; et al.
Abstract : The first β-diketiminato triphosphido diiron complex was synthesized as a versatile molecular single-source precursor for the production of functional FeP that acts as a powerful and durable bifunctional electrocatalyst for water splitting. Abstract : In large-scale, hydrogen production from water-splitting represents the most promising solution for a clean, recyclable, and low-cost energy source. The realization of viable technological solutions requires suitable efficient electrochemical catalysts with low overpotentials and long-term stability for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) based on cheap and nontoxic materials. Herein, we present a unique molecular approach to monodispersed, ultra-small, and superiorly active iron phosphide (FeP) electrocatalysts for bifunctional OER, HER, and overall water-splitting. They result from transformation of a molecular iron phosphide precursor, containing a [Fe2 P3 ] core with mixed-valence Fe II Fe III sites bridged by an asymmetric cyclo-P(2+1) 3− ligand. The as-synthesized FeP nanoparticles act as long-lasting electrocatalysts for OER and HER with low overpotential and high current densities that render them one of the best-performing electrocatalysts hitherto known. The fabricated alkaline electrolyzer delivered low cell voltage with durability over weeks, representing an attractive catalyst for large-scale water-splitting technologies.